Potential Utilization of Catfish Wastewater, Livestock Manure and Waste of Fish as Media and Nutrition for Organic Hydroponic - Gustiar, Fitra; Munandar, Munandar; Ammar, Muhammad; Yakup, Yakup (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
Organic Hydroponics is cultivation on a planting medium without soil with a source of nutrients obtained from the decomposition of organic materials by microorganisms. Catfish cultivation wastewater and agricultural waste can be used as an alternative planting medium and a source of nutrients in organic hydroponic cultivation systems. This study aimed to determine the plant nutrient content in catfish culture wastewater added with cow dung, chicken manure, trash fish waste, and catfish waste; and to determine the growth of mustard greens and lettuce which were cultivated hydroponically in a growing medium of catfish wastewater added with cow dung, chicken manure, trash fish waste, and catfish waste. The results slot deposit 5000 showed that the solution of catfish culture wastewater added with catfish waste contained nutrients N 220.0 ppm, P 166.3 ppm K 154.4 ppm Ca 65.9 ppm Fe 4.4 ppm; catfish culture wastewater added with trash fish waste contains 50.0 ppm N; P 10.8 ppm; K 173.4 ppm; Ca 219.4 ppm and Fe 3.2 ppm; catfish culture wastewater added with cow dung contained nutrients N 300.0 ppm, P 293.4ppm K 1026.8 ppm Ca 413.6 ppm Fe 64.9 ppm, while those given chicken manure included N 100.0 ppm; P 76.1 ppm; K 471.1ppm; Ca 299.9ppm and Fe 27.3ppm. While catfish culture wastewater contains 55.2 ppm of N nutrients; P 6.4 ppm; K 7.0 ppm; Ca 14.2 ppm; Fe 0.4 ppm. The growth of lettuce in the growing media of catfish culture wastewater given trash fish and catfish was relatively the same, namely 37.7% and 37.9%, respectively. Meanwhile, the growth of mustard pakcoy grown on planting media given chicken manure (47.6%) was higher than the growth of mustard pakcoy grown on cow dung (33.3%). The addition of 50% ABmix nutrients increased the growth of mustard pakcoy on media that was given chicken manure by 81.7%; pakcoy on media that was given cow dung waste by 74.8%; Meanwhile, the addition of ABmix 50% nutrients increased the growth of lettuce on media that was given catfish meal by 64.4%, and on media that was given trash fish meal by 61.9%. Research shows a high potential for using organic waste as a medium and source of organic hydroponic cultivation fertilizer.